Bioactive metabolites from the leaves of Withania adpressa. (1st January 2018) - Ben Bakrim, Widad; El Bouzidi, Laila; Nuzillard, Jean-Marc; Cretton, Sylvian; Saraux, Noémie; Monteillier, Aymeric; Christen, Philippe; Cuendet, Muriel; Bekkouche, Khalid
Abstract: Context: Withania (Solanaceae) species are known to be a rich source of withanolides, which have shown several biological properties. Objective: To identify the compounds responsible for Withania adpressa Coss. antioxidant activity and further test them for their NF-κB inhibition and antiproliferative activity in multiple myeloma cells. Materials and methods : Compounds were obtained from the EtOAc extract of W. adpressa leaves. Structure elucidation was carried out mainly by 1D- and 2D-NMR, and mass spectrometry. Isolated compounds were tested in a dose-response for their in vitro NF-κB inhibition and antiproliferative activity in multiple myeloma cells after 5 and 72 h treatment, respectively. Results: The fractionation resulted in the isolation of a new glycowithanolide named wadpressine (5 ) together with withanolide F, withaferin A, coagulin L, and nicotiflorin. The latter showed a moderate ability to scavenge free radicals in DPPH (IC50  = 35.3 µM) and NO (IC50  = 41.3 µM) assays. Withanolide F and withaferin A exhibited low µM antiproliferative activity against both multiple myeloma cancer stem cells and RPMI 8226 cells. Furthermore, they inhibited NF-κB activity with IC50 values of 1.2 and 0.047 µM, respectively. The other compounds showed a moderate inhibition of cell proliferation in RPMI 8226 cells, but were inactive against cancer stem cells and did not inhibit NF-κB activity. Discussion and conclusions: One new glycowithanolide and four known compounds were isolated. Biological evaluation data gave further insight on the antitumor potential of withanolides for refractory cancers.